مدى تأثير الترويج الإلكتروني على سلوك المستهلك الجزائري دراسة حالة وكالة بابل للسياحة والأسفار - خولة بلواعر (My University, 2021)
aim of this study was to know the role of an electronic mix of an electronic mix of consumer behavior from the point of view of this latter, and therefore identifies the electronic promotional elements of e-mail, electronic advertising and electronic public relations and activating electronic sales and effective sales Items on consumer behavior in responding to these electronic means according to model .)Aida( attention, desire, act and known as a short term model attention There is a statistically significant relationship in the emergence of an electronic promotion on the behavior of Algerian consumer, as well as we have emerged that electronic selling elements are more influential on consumer behavior، m, followed by electronic advertising, then electronic public relations, and finally the activation of electronic sales. ...................................................... كان الهدف من هذه الدراسة هو معرفة دور المزيج الترويجي الالكتروني في تاثيره على سلوك المستهلك من وجهة نظر هذا الاخير، و بالتالي التعرف على عناصر المزيج الترويجي الالكتروني و المتمثلة في البيع الشخصي الالكتروني و الاعلان الالكتروني و العلاقات العامة الالكترونية و تنشيط المبيعات الكترونيا و تاثير هذه العناصر على سلوك المستهلك في الاستجابة لهذه الوسائل الالكترونية وفق نموذج .)AIDA الانتباه، الاىتمام، الرغبة، والفعل و المعروف اختصارا بنموذج ) هناك علاقة ذو دلالة احصائية في تاثير المزيج الترويجي الالكتروني على سلوك المستهلك الجزائري، كذلك ظهر لنا ان البيع الشخصي الالكتروني اكثر عناصر الترويج الالكتروني تأثيرا على سلوك المستهلك ويليو الاعلان الالكتروني ثم العلاقات العامة الالكترونية و أخيرا تنشيط المبيعات الالكترونية